MODEL PENYELENGGARAAN PENDIDIKAN SEKOLAH ISLAM TERPADU (STUDI KASUS DI SDIT AL-BIRUNI MAKASSAR) - Farida Hanum (Jurnal Dialog, 2015)
This study aims at determining an alternative model of education in SDIT Al-Biruni Makassar in South Sulawesi by utilizing qualitative methods. The results of this study indicated that: (a) Integrated Islamic school model that incorporates general and religious subjects is able to generate students with competitive excellences in academics, non-academics, religion and social relation; (b) the access to this alternative model of education is currently limited to wealthy Muslims, due to the expensive school fees, (c) the Ministry of Religious Affairs should provide constructive supports to the alternative model of Islamic schools developing in the community.